Molecular docking studies and ADME-Tox prediction of phytocompounds from Merremia peltata as a potential anti-alopecia treatment - Syawal Abdurrahman; Ruslin Ruslin; Aliya Nur Hasanah; Resmi Mustarichie (Wolters Kluwer Medknow Publications, 2021)
Alopecia is a condition in which some or all of the hair from the scalp is lost. One recent preventative measure is the inhibition of the enzyme 5-α-reductase. Inhibition of the enzyme 5-α-reductase converts circulating testosterone to its more potent metabolite, dihydrotestosterone. Ethnobotically, Merremia peltata is used as a baldness medicine by utilising compounds contained within the leaves. This research aimed to test activity of 18 known compounds contained within M. peltata) as anti-alopecia. Activity was based on their interaction with the androgen receptor (PDB code 4K7a) using molecular docking and ADME-Tox prediction. The stages of research performed were: preparation of androgen protein structure databases; preparation and optimization of three-dimensional structures of compounds using ChemDraw 8.0; molecular docking to the androgen receptor protein using Autodock 1.5.6.; and ADME-Tox prediction using the pkCSM tool. The following test compounds had strong bond energies (ΔG): compound 16 (olean-12-en-3beta-ol, cinnamate)-7.71 kcal/mol, compound 17 (alpha-amyrine)-6.34 kcal/mol, and Finasteride-6.03 kcal/mol. Interestingly, the ΔG of compound 16 (olean-12-en-3beta-ol, cinnamate) is better than of minoxidil (-4.8 kcal/mol) and also to gold-standard treatment compound, finasteride. ADME-Tox prediction for compound 16 showed favorable results in several metrics such as skin permeability, absorption, and distribution. Compound 16 (olean-12-en-3beta-ol, cinnamate) is therefore a potential androgen receptor antagonist and may be beneficial in the treatment of alopecia.